Realization of Mykola Mykolayovych Darmanskyi when Organizing and Conducting Pedagogical Practice in Khmelnytskyi Humanitarian-Pedagogical Academy - Kazakova, Nataliya (Pedagogical Discourse, 2014)
Short informative facts about peculiarities of organization of pedagogical practice from the period of establishment of pedagogical courses in Proskurov (1921) to Khmelnitsky humanitarian-pedagogical academy (2006) formation have been represented in the article. Mykola Mykolayovych Darmanskiy ideas about the necessity of pedagogical school and higher educational establishment rapprochement. The article deals with the topical problem of organization and conducting pedagogical practice of the future teachers under the conditions of multi-level education. The main ideas of Mykola Mykolayovych Darmanskyi as for organization and conducting pedagogical practice in multi-level educational establishment and directing realization of their activity by the personnel of the department of pedagogical practice in Khmelnytskyi Humanitarian-Pedagogical Academy have been revealed in the article. To these belong: organizational, methodological, scientific work with the students, supervisors of practice of the academy, and the practice bases; analysis of the results of practice; control and practice supervision.